Geometry of large Boltzmann outerplanar maps. Issue 3 (11th December 2018) - Stefánsson, Sigurdur Örn; Stufler, Benedikt
Abstract : We study the phase diagram of random outerplanar maps sampled according to nonnegative Boltzmann weights that are assigned to each face of a map. We prove that for certain choices of weights the map looks like a rescaled version of its boundary when its number of vertices tends to infinity. The Boltzmann outerplanar maps are then shown to converge in the Gromov‐Hausdorff sense towards the α ‐stable looptree introduced by Curien and Kortchemski (2014), with the parameter α depending on the specific weight‐sequence. This allows us to describe the transition of the asymptotic geometric shape from a deterministic circle to the Brownian tree.